Management of chickpea Ascochyta blight using fungicides and cultivar resistance improves grain yield, quality, and grower profitability - Fanning, Joshua; Brand, Jason; Munoz Santa, Isabel; McDonald, Linda; Taylor, Julian; Hollaway, Grant (Frontiers in Plant Science, 2022)
International production of chickpea is under constant threat from the fungal disease Ascochyta blight (Ascochyta rabiei). In Australia, there is limited cultivar resistance, and disease management is reliant on foliar applied fungicides. Several recently registered fungicides in Australia that combine active ingredients with different modes of actions, have been shown to have curative properties. In this study, in the presence of Ascochyta blight, disease severity, grain yield and quality were measured and the subsequent gross margin for growers calculated in seven field experiments conducted in Victoria (Australia) across three seasons. These experiments investigated the effects of: two cultivars with differing disease resistance (PBA Striker and Genesis 090), and several fungicide strategies for the control of Ascochyta blight. Fungicides that combine different modes of actions (Tebuconazole + Azoxystrobin, Bixafen + Prothioconazole and Fludioxonil + Pydiflumetofen) were applied before a rainfall event (preventative) or after the first signs of disease (post-infection). Older, single active fungicides compared included Captan, Chlorothalonil and Propiconazole, all applied preventatively. Maximum disease severities ranged from 87% at Horsham and 94% at Curyo across the three seasons with Nhill recording 87% during 2020. Demonstrating the benefit of cultivar resistance for Ascochyta blight management, grain yield losses were substantially lower in the partially resistant cultivar Genesis 090 (64%) compared to the susceptible cultivar PBA Striker (96%), at Curyo in 2020. The preventative fungicide strategies reduced grain yield losses from 96% and 64% to 51% and 15% for PBA Striker and Genesis 090, respectively, demonstrating the benefit of fungicides in Ascochyta blight management. Across seasons and environments, a comparison between fungicides applied preventatively or post-infection highlighted both were both profitable ($23/ha to $1,095/ha), except when dry conditions limited grain yield to less than 0.6 t/ha. The post infection timing had greater yield losses in sites/seasons with higher rainfall, but with dual active ingredient fungicides and partially resistant cultivars this timing could allow a reduction in the number of fungicide applications, thus improving profitability. These experiments highlighted the importance of controlling Ascochyta blight through cultivar resistance and fungicides to improve grain yields, grain quality and grower profitability.